Three new species in the leafhopper genus Pedionis Hamilton(Hemiptera: Cicadellidae: Macropsinae) from China, with a key to Chinese species - Yang, Liyuan; Zhang, Yalin (Zootaxa, 2014)
Three new species, Pedionis (Pedionis) tribrachyblasta, P. (P.) dentiforma and P. (P.) dinghuensis spp. nov. are recorded from China. Images of adults and genitalia of the three species are provided, with a key to distinguish all male species in this genus from China.